La responsabilidad social como modelo de gestión en las empresa públicas eléctricas y su incidencia en el desarrollo local sostenible - Flores Herrera, Carlos Bolívar (2014)
The Constitution of the Republic of Ecuador (2008) introduces in Articles 66 (literals 15 and 26), 204 and 278 (lit.2) the concept of social responsibility as a requirement of the right to development of economic activities, as individually or collectively, as the principles of solidarity, social and environmental responsibility; mandate that must be implemented within the framework of a new model of development of the country, based on equity, equal rights, economic, social, cultural inclusion, etc., dimensions framed in good living. The constitutional umbrella has now allowed the Ecuadorian public electricity sector companies through its Business Units incorporate social responsibility as a strategic element in managing their mission and vision; which is a first step that will enable the configuration of a model of social management within them.